Dissolved organic carbon in Alaskan Arctic snow: concentrations, light-absorption properties, and bioavailability. Issue 1 (1st January 2020) - Zhang, Yulan; Kang, Shichang; Gao, Tanguang; Sprenger, Michael; Dou, Tingfeng; Han, Wei; Zhang, Qi; Sun, Shiwei; Du, Wentao; Chen, Pengfei; Guo, Junming; Cui, Xiaoqing; et al.
Abstract: Dissolved organic carbon (DOC) plays an important role in the carbon cycle, radiative forcing, and biogeochemistry in cryospheric regions. In this study, concentrations, light-absorption properties and bioavailability of DOC from snow cover in Alaska were characterized. Results indicated that average concentrations of DOC in snow of Alaska (0.17 − 0.30 mg L −1 ) were lower than that found in Asian mountainous glaciers, but higher that found from polar regions snow. No significant trend of DOC was observed during April to May in 2017 due to the short term study; while the vertical variations generally showed a little higher values in the surface snow than that in the sub-surface snow. An obvious characteristic of DOC light-absorbance in snow between the wavelength of 300 and 700 nm indicated the mass absorption cross section of DOC at 365 nm (MACDOC365 ) was 0.32 ± 0.24 and 0.37 ± 0.32 m 2 g −1 for the snow cover at Barrow site (Arctic Ocean coast) and the other Alaskan regions, respectively. The MACDOC365 values increased especially during snow melting, indicating the DOC with high MAC values were prone to retain in snow. The proportion of radiative forcing caused by DOC relative to that by black carbon in snow was approximately 2.3%, indicating that DOC in snow should be considered during the accelerated melt of snow cover. The bioavailability experiment of DOC in snow indicated that DOC may be an important bioavailable source for proglacial and coastal ecosystems in Alaskan Arctic regions. Using backward air mass trajectory analysis, we suggested that DOC deposited in snow at Barrow primarily originates from marine or terrestrial air mass, but the specific contribution of different sources cannot be quantified without data related to the DOC's chemical composition and carbon isotopic signatures. This study highlighted the climatic implications of DOC in snow in the Arctic regions.